Structural damage classification in composite materials using the Wigner-Ville distribution and convolutional neural networks - Monson, Paulo Monteiro de Carvalho; Conceição Junior, Pedro de Oliveira; Lofrano Dotto, Fabio Romano; Aguiar, Paulo Roberto de [UNESP]; Rodrigues, Alessandro Roger; David, Gabriel Augusto (Elsevier, 2024)
Detecting damage in composite materials is crucial and has received considerable attention in the field of machine learning. However, challenges remain in addressing backbone issues and classifying specific types of damage. This paper presents a novel deep-learning approach for automatically distinguishing delamination and microcracks in Carbon Fiber-Reinforced Polymer (CFRP). The methodology utilizes signals from piezoelectric transducers transformed into time–frequency representations based on the Wigner-Ville Distribution (WVD). Backbone issues were successfully addressed by transitioning the time series classification problem into a computer vision (CV) context through Convolutional Neural Networks (CNN). The analysis included a thorough examination of delamination and microcracks datasets produced experimentally by the National Aeronautics and Space Administration (NASA), focusing on these two types of damage. The proposed methodology achieved a precision range of 98.3 % to 100 % in damage classification, demonstrating its effectiveness for structural health monitoring in composite materials.
Keywords: Composite; Deep Learning; Failure; Fatigue